Bimbingan dan Konseling Keagamaan Bagi Wanita Korban Kekerasan Seksual - Khoiroh, Anikmatul (Institut Agama Islam Syarifuddin Lumajang, 2021)
Unrest in the community regarding sexual violence against women and its handling by providing rehabilitation, one by providing religious guidance and counseling, because religion is one of the media used for behavioral therapy and mental or psychological healing. Through a qualitative research method with a field research approach, the author examines the process of religious guidance and counseling for women victims of sexual violence, as well as the results after being given religious guidance and counseling to women victims of sexual violence. The results of the study found that the process of religious guidance and counseling to clients is given by strengthening nature and faith by praying, worshiping, reading and understanding the scriptures and giving motivation to clients to get closer and surrender to Allah, by adjusting their various profiles. both in terms of problems, age, and client's condition. However, the results or changes are influenced by the victim's cognitive level or knowledge of religious teachings, and the mental condition factors that experience mental disorders. The professionalism of the counselor in providing religious guidance and counseling can also have an influence on the success of the counseling process so that the client's feelings become calmer and can accept his situation. Keywords: Religious Guidance and Counseling, Women Victims of Sexual Violence.